Review on Energy and Exergy Analysis of Air and Water Based Photovoltaic Thermal (PVT) Collector - Muslizainun Mustapha; Ahmad Fudholi; Chan Hoy Yen; Mohd Hafidz Ruslan; Kamaruzzaman Sopian (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In photovoltaic thermal hybrid (PV/T) collectors, the electricity and thermal energy are produce simultaneously. PV/T technology has been proven in previous studies where it could give benefits for high energy demand supplementary. For example, in space heating, domestic water heating and also drying. The PVT collectors can be classified into air-based PVT, water-based PVT and dual-fluid (air+water) PVT collector. In this paper, the analysis of energy and exergy efficiency of PVT collectors are compiled and reviewed. This study has found that generally the energy and exergy efficiency are range from 40%-70% and 5%-20%, respectively.